Rescue of silenced UCHL1 and IGFBP4 expression suppresses clonogenicity of giant cell tumor-derived stromal cells - Fellenberg, Jörg; Sähr, Heiner; Liu, Li; Schönsiegel, Frank; Depeweg, Daniela; Lehner, Burkhard; Herr, Ingrid (Cancer letters, 2013)
Giant cell tumor (GCT) of bone is a generally benign tumor with a locally aggressive behavior. Histologically, GCTs consist of multinucleated giant cells, mononuclear histiocytes and the neoplastic fibroblast-like stromal cells (GCTSC). Growing evidence exists that GCTSCs develop from mesenchymal stem cells (MSCs), but little is known about the underlying molecular mechanisms. In previous studies we observed inactivation of the ubiquitin carboxyl-terminal hydrolase L1 (UCHL1) gene in primary GCTSC due to strong DNA hypermethylation, indicating that epigenetic silencing might be involved in neoplastic transformation of MSCs. Here we investigated further candidate genes and identified strong hypermethylation of the insulin-like growth factor binding protein 4 (IGFBP4) promoter, resulting in IGFBP4 downregulation in GCTs compared to MSCs. Overexpression of UCHL1 and IGFBP4 by stable transfection of GCTSC did not influence cell viability, proliferation, migration and chemosensitivity compared to parental cells. However, colony-formation was significantly decreased suggesting that rescue of UCHL1 and IFGBP4 suppresses clonogenicity of GCT stromal cells. The observation of reduced expression of the stem-cell-specific transcription factors OCT4 and SOX2 in these cell lines further supported our findings. Epigenetic silencing of UCHL1 and IGFBP4 in GCTs might thus be a crucial event during the malignant transformation of MSCs in the context of GCT development and represent promising targets for the development of new diagnostic and therapeutic strategies.
Gesehen am 12.03.2021